THE INFLUENCE OF LEARNING ORGANIZATION AND KNOWLEDGE MANAGEMENT ON STUDENT LEARNING INNOVATION WITH LEARNING CREATIVITY AS A MEDIATING VARIABLE IN ISLAMIC RELIGIOUS HIGHER EDUCATION INSTITUTIONS IN KUBU RAYA - Fathur Rohman; Munirul Abidin (Jurnal Manajemen Pendidikan, 2026)
The development of the era of disruption requires PTKI to adapt through learning innovation. This study analyzes the influence of learning organization and knowledge management on student learning innovation with learning creativity as a mediating variable at PTKI in Kubu Raya Regency. Referring to the Theory of Planned Behavior, this study uses an associative quantitative approach with PLS-SEM analysis through SmartPLS 4. Data were collected from 100–200 active students using a Likert scale questionnaire. The results show that knowledge management has a significant positive effect on learning creativity (β = 0.939), while learning organization has a weak negative effect (β = -0.004). Learning creativity acts as a strong mediator of learning innovation (β = 0.875) with R² 0.788. These findings underscore that the effectiveness of knowledge management and the strengthening of creativity are key factors in increasing learning innovation, while the strengthening of a learning organization culture still needs to be improved through transformational leadership and appreciation of creative ideas.